The Escherichia coli phylogenetic group B2 with integrons prevails in childhood recurrent urinary tract infections. Issue 5 (11th September 2013) - Kõljalg, Siiri; Truusalu, Kai; Stsepetova, Jelena; Pai, Kristiine; Vainumäe, Inga; Sepp, Epp; Mikelsaar, Marika
<x xml:space="preserve">Abstract</x> The aim of our study was to characterize the phylogenetic groups of Escherichia coli, antibiotic resistance, and containment of class 1 integrons in the first attack of pyelonephritis and in subsequent recurrences in young children. Altogether, 89 urine E. coli isolates from 41 children with urinary tract infection (UTI) were studied for prevalence and persistence of phylogenetic groups by pulsed‐field gel electrophoresis (PFGE), antibacterial resistance by minimal inhibitory concentrations (MIC) and class 1 integrons by PCR. Phylogenetic group B2 was most common (57%), followed by D (20%), A (18%) and B1 (5%). Overall resistance to betalactams was 61%, trimethoprim‐sulfamethoxazole 28%, and was not associated with phylogenetic groups. According to PFGE, the same clonal strain persisted in 77% of patients. The persistence was detected most often in phylogenetic group B2 (70%). Phylogenetic group B2 more often contained class 1 integrons than group A. Integron positive strains had higher MIC values of cefuroxime, cefotaxime, and gentamicin. In conclusion, phylogenetic group B2 was the most common cause of the first episode of pyelonephritis, as well as in case of the persistence of the same strain and contained frequently class 1 integrons in childhood recurrent UTI. An overall frequent betalactam resistance was equally distributed among phylogenetic groups.